Production of octyl levulinate biolubricant over modified H-ZSM-5: Optimization by response surface methodology - Nandiwale, Kakasaheb Y.; Yadava, Sunil K.; Bokade, Vijay V. (Journal of Energy Chemistry, 2014)
The present study highlighted the use of modified H-ZSM-5 (Meso-HZ-5) as heterogeneous catalyst for the synthesis of octyl levulinate biolubricant by catalytic esterification of biomass derived renewable levulinic acid (LA) with n-octanol. The process variables such as catalyst loading (X-1), n-octanol to LA molar ratio (X-2) and reaction temperature (X-3) were optimized through response surface methodology (RSM), using Box-Behnken model. Analysis of variance was performed to determine the adequacy and significance of the quadratic model. The yield of octyl levulinate was obtained to be 99% at optimum process parameters. The developed quadratic model was found to be adequate and statistically accurate with correlation value (R-2) of 0.9971 to predict the yield of octyl levulinate biolubricant. The study was also extended on the validation of theoretical and experimental data, including catalyst reusability.
Keywords: biolubricant; Esterification; H-ZSM-5; levulinic acid; octyl levulinate; Response surface methodology